Adenocarcinoma of the Urachus: A Primary Not to Overlook - Alves, AS (2022)
Urachal carcinoma is a rare and aggressive neoplasm, involving the urachus, a remnant of the fetal genitourinary tract that extends from the umbilicus to the dome of the bladder. We present a 49-year-old woman with a history of pelvic discomfort and a palpable suprapubic mass. Pelvic ultrasound and magnetic resonance revealed a 55-mm midline supravesical mass, arising from the urachus and extending inferiorly through the bladder. The characteristics of the mass and its location favored the diagnosis of urachal carcinoma. There were no regional or distant metastases. The patient underwent surgical resection of the tumor and histopathological examination confirmed the diagnosis of a non-cystic enteric type urachal adenocarcinoma. The purpose of this article is to present a case of primary adenocarcinoma of the urachus, describe its epidemiology and clinical features, as well as illustrate its key imaging findings along with pathologic correlation